The Longitudinal Study of Earnings Management: Analysis on Companies Financial Abilities - Nik Mohd Norfadzilah, Nik Mohd Rashid; Rohaya, Md Noor; Norazam, Matsuki (2016)
The aim of this paper is to provide empirical evidences of the relationships between the financial abilities towards in the financial statement to the earnings management level (EM) among of public sector companies on Bursa Malaysia from year 2001 until 2012. Primarily, the initial samples comprised 375 selected public listed companies with 4500 firm-years observation. From the samples, those companies who have not implied with the earnings management activities was excluded as a sample of the study. Thus, the final sample of this study was comprises 3971 firm-years observation. The study was adopted the Kothari Model as a measurement model for earnings management level in the business organization. Meanwhile, the findings of this study indicated significant relationships between earnings ability (EAB), financial structure's ability (FSAB), debt repaying ability (DRAB) and non-financial factors (NFF) towards the earnings management level (EM) in the business organization. Therefore, these evidences can be used as new financial mechanisms to potential and existing stakeholders in order to assist them for any decision making purposes.